Bilingual Learning in Global English Class Learning Communities for Elementary School Level Children - Ali Ma'sum Effendi; Setia Rini; Erna Risfaula Kusumawati (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
The era of industrial revolution 4.0 requires the mastery of science and technology so that mastering bilingualism becomes one of the most important needs of human life. A bilingual education program is an attempt to introduce children to a second language, especially English, which is implemented in education and training. The purpose of this study is to: (1) explore in depth the management implemented in the Global English Class Learning Community at the primary school age. (2) describes the implementation of bilingual education for elementary school children. (3) description of the results of the implementation of bilingual education among preschool children. This type of research is qualitative with an ethnographic approach, which is a method of deciphering and interpreting the system of emerging cultural or social groups. The subjects of this study were primary school children and teachers of the Global English Class Learning Community. The results of the study show that bilingual education in the Global English Class Learning Community has a positive effect on primary school children. The concept is used in different models, such as group learning, peer learning, field trips, mother tongue learning. The implementation of bilingual education in Global English Class shows a positive effect and is very useful for primary school children in acquiring the child's bilingual language.